Enhancement of motionability based on segregation of states for holonomic soccer robot - Gunawan Dewantoro; Anton Suprayudi; Daniel Santoso (National Research and Innovation Agency, 2018)
One of the critical issues when navigating wheeled robot is the ability to move effectively. Omnidirectional robots might overcome these nonholonomic constraints. However, the motion planning and travel speed of the movement has been in continuous research. This study proposed segregation of states to improve the holonomic motion system with omnidirectional wheels, which is specially designed for soccer robots. The system used five separate defined states in order to move toward all directions by means of speed variations of each wheel, yielding both linear and curved trajectories. The controller received some parameter values from the main controller to generate robot motion according to the game algorithm. The results show that the robot is able to move in an omnidirectional way with the maximum linear speed of 3.2 m/s. The average error of movement direction is 4.3°, and the average error of facing direction is 4.8°. The shortest average time for a robot to make a rotational motion is 2.84 seconds without any displacement from the pivot point. Also, the robot can dribble the ball forward and backward successfully. In addition, the robot can change its facing direction while carrying the ball with a ball shift of less than 15 cm for 5 seconds. The results shows that state segregations improve the robots capability to conduct many variations of motions, while the ball-handling system is helpful to prevent the ball gets disengaged from the robot grip so the robot can dribble accordingly.